Model Eco-Nutri: Pendampingan Manajemen Lahan Sempit Untuk Ketahanan Pangan Keluarga dan Pencegahan Stunting - Merry Moy Mita; Nila Sari (CV. Armas Suan Sejahtera, 2025)
Stunting remains a significant national challenge in Indonesia, with a prevalence rate of 21.5% in 2023, where high food costs and the mismanagement of household assets such as underutilized small yards contribute to the vulnerability of toddler nutrition in rural areas like Adin Tengah Village. This community service program aimed to integrate economic management principles with public health interventions to foster household food self-sufficiency and mitigate stunting risks through the implementation of the